Aspects of interaction with melt zalizonikelkysnevyh 4d-metal - Zr, Nb, Mo - Шаркіна, Н.О.; Манчук, Н.М.; Судавцова, В.С. (Proceedings of National Aviation University (archive), 2006)
There are the results of investigation of deoxidizing ability of 4d–metals in Fe–Ni–O melting systems (invars) carried out by calorimetry method in isoparabolic calorimeter at 1873 K.